Analysing Fronto Temporal Dementia Using Artificial Neural Networks - N, Sandhya; Nagarajan.S, Dr (International Journal of Engineering and Technology, 2018)
This study aims at studying Fronto Temporal Dementia (FTD) which occurs because of neuro degeneration process. The data of a 60 year old patient including the patient’s previous medical history, Neurological examination, Neuro-psychological examinations, and pathological tests along with brain images are obtained. The disintegrations in the demented brain show that neurons fail to transmit signals resulting in loss of network connectivity and reduced functionality of the brain regions. The demented brains are compared against healthy controls (HC). We propose standard back propagation algorithm to compare the demented brain with the Healthy Controls. The mathematical analysis is done.